2000
DOI: 10.1080/010503900750022907
|View full text |Cite
|
Sign up to set email alerts
|

Severe-profound hearing impairment and health-related quality of life among post-lingual deafened Swedish adults

Abstract: Health-related quality of life (HRQL) was measured with the Nottingham Health Profile (NHP) in 311 Swedish adults suffering from severe-profound hearing impairment (sensorineural hearing loss in the better ear of > or = 70 dB HL at a frequency of 1.0 kHz) for comparisons with a normal-hearing population. The subjects completed NHP and a questionnaire regarding bio-psycho-social status. Generally, subjects with profound hearing loss reported lower HRQL. Significant differences were obtained for lack of energy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 19 publications
3
47
0
1
Order By: Relevance
“…He stated that there is an urgent need for additional research to address the issue of quality of life among people with hearing impairment. Ringdahl and Grimby [24] and Grimby and Ringdahl [25] reported that patients with severe hearing loss constitute a potential risk group for general deterioration in quality of life. However, subjects with severe-profound hearing loss in the study, who were fully employed, reported higher levels of health-related quality of life than subjects with similar hearing loss who were pensioned.…”
Section: Introductionmentioning
confidence: 99%
“…He stated that there is an urgent need for additional research to address the issue of quality of life among people with hearing impairment. Ringdahl and Grimby [24] and Grimby and Ringdahl [25] reported that patients with severe hearing loss constitute a potential risk group for general deterioration in quality of life. However, subjects with severe-profound hearing loss in the study, who were fully employed, reported higher levels of health-related quality of life than subjects with similar hearing loss who were pensioned.…”
Section: Introductionmentioning
confidence: 99%
“…[13][14][15][16] According to Ringdahl,17 it appears to be a condition that places these individuals in a risk group for psychosomatic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, resultados diferentes foram apresentados em outra pesquisa 17 , com relação à influência da perda auditiva na QVRS. De modo geral, os indivíduos com perda auditiva profunda relataram menor QVRS.…”
Section: Artigos Que Investigaram a Qualidade De Vida Com Instrumentounclassified